2019
DOI: 10.1101/567800
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Translational products encoded by novel ORFs may form protein-like structures and have biological functions

Abstract: Translation products encoded by non canonical or novel open reading frame (ORF) genomic regions are generally considered too small to play any significant biological role, and dismissed as inconsequential. In this study, we show that mutations mapping to novel ORFs have significantly higher pathogenicity scores than mutations in protein-coding regions. Importantly, novel ORFs can translate into protein-like structures with putative independent biological functions that can be of relevance in disease states, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Results from our own work 23 and from others have indicated that nORF transcripts are indeed expressed at a lower abundance compared to already fixed known protein coding transcripts 2 , 3 and their expression is not ‘noisy’—increased standard deviation versus mean—to be dismissed as inconsequential for biological functions. nORF transcripts are shown to become fixed 24 , 25 and we have shown that some nORFs can express noncanonical proteins that can be biologically regulated with potential functions 10 , 26 thus indicating that there might be a selection process. However, some studies, including ours, have demonstrated that nORF encoded proteins have propensity for increased disorder 27 than known canonical proteins, hence, it is not clear whether the noncanonical proteins contribute to the fitness of the organisms, or whether their biological activities are effectively neutral without any deleterious consequences.…”
Section: Introductionmentioning
confidence: 91%
“…Results from our own work 23 and from others have indicated that nORF transcripts are indeed expressed at a lower abundance compared to already fixed known protein coding transcripts 2 , 3 and their expression is not ‘noisy’—increased standard deviation versus mean—to be dismissed as inconsequential for biological functions. nORF transcripts are shown to become fixed 24 , 25 and we have shown that some nORFs can express noncanonical proteins that can be biologically regulated with potential functions 10 , 26 thus indicating that there might be a selection process. However, some studies, including ours, have demonstrated that nORF encoded proteins have propensity for increased disorder 27 than known canonical proteins, hence, it is not clear whether the noncanonical proteins contribute to the fitness of the organisms, or whether their biological activities are effectively neutral without any deleterious consequences.…”
Section: Introductionmentioning
confidence: 91%
“…Results from our own work (manuscript in review) and from others have indicated that nORF transcripts are indeed expressed at a lower abundance compared to already fixed known protein coding transcripts 3,4 and their expression is not ‘noisy’ to be dismissed as inconsequential for biological functions. nORF transcripts are shown to become fixed 24,25 and we have shown that some nORFs can express noncanonical proteins that can be biologically regulated with potential functions 11 26 thus indicating that there might be a selection process. However, some studies, including ours, have demonstrated that nORF encoded proteins have propensity for increased disorder 27 than known canonical proteins, hence, it is not clear whether the noncanonical proteins contribute to the fitness of the organisms, or whether their biological activities are effectively neutral without any deleterious consequences.…”
Section: Introductionmentioning
confidence: 93%
“…There have also been recent advances in the sensitivity of proteomics methods such as ribosome profiling and mass spectrometry (MS), the ability to sequence genomes and transcripts at a deeper depths, and in the ability to integrate these two data types, which our lab specializes in and calls Systems Proteogenomics (Prabakaran et al 2014). These advances have revealed that we have underestimated the genome's coding potential, with many unannotated ORFs showing evidence of translation in humans alone (Ma et al 2014;Jagannathan et al 2019;Erady et al 2019;Chen, J. et al, 2020). These ORFs are mostly under 100 codons and found in diverse regions of the genome, including in long noncoding RNAs (lncRNAs), pseudogenes, 3'UTRs, 5'UTRs, and alternative reading frames of canonical protein coding exons (Prabakaran et al 2014;Brunet et al 2018;Plaza et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The functional evidence which does exist has implicated nORFs in roles both related to and independent of nearby canonical genes (Brunet et al 2018), including mRNA decapping (Pueyo et al 2016), muscle regeneration (Matsumoto et al 2017), and insulin secretion (Hu et al 2016). Additionally, we have shown previously that nORF encoded protein-like products can form structures with potential biological functions (Erady et al 2019), can be regulated by post-translational modifications (Jagannathan et al 2019), are biologically regulated in mouse neurons (Prabakaran et al 2014), and harbour deleterious mutations from cancer and other inherited diseases (Jagannathan et al 2019;Erady et al 2019).…”
Section: Introductionmentioning
confidence: 99%